2010
DOI: 10.1186/1471-230x-10-53
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive index of liver fibrosis induced by alcohol, thioacetamide and schistosomal infection in mice

Abstract: BackgroundNon invasive approaches will likely be increasing utilized to assess liver fibrosis. This work provides a new non invasive index to predict liver fibrosis induced in mice.MethodsFibrosis was generated by thioacetamide (TAA), chronic intake of ethanol, or infection with S. mansoni in 240 mice. Both progression and regression of fibrosis (after treatment with silymarin and/or praziquantel) were monitored. The following methods were employed: (i) The METAVIR system was utilized to grade and stage liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…Together, using TAS cut-off values, the diagnostic accuracy of significant fibrosis and cirrhosis in accordance to liver biopsy were reported in 86.7 and 81.3 % of CHC patients respectively. The data obtained revealed like others, that oxidative stress markers, antioxidant enzymes and hydroxyproline have been documented to play a part in the pathogenesis of CHC [5,13,20,34].…”
Section: Discussionsupporting
confidence: 78%
“…Together, using TAS cut-off values, the diagnostic accuracy of significant fibrosis and cirrhosis in accordance to liver biopsy were reported in 86.7 and 81.3 % of CHC patients respectively. The data obtained revealed like others, that oxidative stress markers, antioxidant enzymes and hydroxyproline have been documented to play a part in the pathogenesis of CHC [5,13,20,34].…”
Section: Discussionsupporting
confidence: 78%
“…S. mansoni infection resulted in egg deposition with formation of dense granulomatous mass surrounding the deposited egg and intense hepatic reaction. Hessien et al (2010) reported similar increase in hepatic hydroxyproline and collagen due to S. mansoni-induced Mice were infected by subcutaneous injection of 60 ± 10 cercariae/ mouse, left for 28 days, and then treatment started and persisted for another 4 weeks…”
Section: Discussionmentioning
confidence: 75%
“…The absorbance of the reddish purple complex was measured at 550 nm. Liver collagen content was calculated according to Hessien et al (2010). The collagen content was calculated by multiplying the hydroxyproline concentration by 7.46, where this imino acid represents 13.4% of collagen.…”
Section: Measurement Of Liver Hydroxyproline Contentmentioning
confidence: 99%
“…To validate the in vivo effects of etanercept-secretome, we generated in vivo model of liver fibrosis by subcutaneous injection of TAA (200 mg/kg, three times a week for 8 weeks) into experimental mice [31][32][33][34][35][36]. Subsequently, control mice (n = 30) and TAA-treated mice (n = 30) received four injections (two times a week during 7th and 8th week of TAA treatment) of 0.1 mL normal saline (n = 10), 0.1mL control secretome (n = 10), and 0.1mL etanercept-secretome (n = 10), respectively.…”
Section: Effects Of the Etanercept-secretome In An In Vivo Liver Fibrmentioning
confidence: 99%